Interdiffusion behavior in sigma-phase using Ni3Al/Mo diffusion couples - Zhou C.; Gong W.; Huang S.; Wei H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The sigmaNiMo( Al) phase was formed using Ni3Al/Mo diffusion couples at 1423, 1473 and 1523 K. The growth of formed phase and the concentration-distance profiles for each component in the diffusion couples were examined by electron probe microanalysis (EPMA). The activation energy for the parabolic growth of σ phase is found to be 525.3 kJ/mol. The concentration dependence and average ternary interdiffusion coefficients in single σ-NiMo(Al) phase were calculated, and the Arrhenius equations of the D for the σ-NiMo(Al) phase are calculated, the diffusional interaction between Ni, Mo and Al in σ-NiMo(Al) phase was studied by the crossinterdiffusion coefficients. Moreover, these results were utilized to explain the σ phase formation and growth in γ’ phase.